INVENTARISASI ZINGIBERACEAE DI KAWASAN HUTAN TEMBAWANG DESA SUMBER KARYA KECAMATAN TERIAK KABUPATEN BENGKAYANG - Andini, Veronika; Rafdinal, Rafdinal; Turnip, Masnur (Jurnal Protobiont, 2020)
Zingiberaceae is the family of flowering plants commonly known by the people of Indonesia as the Jahejahean. This plant is widely used for many things such as spices, medicine, ornamental plants, cosmetic ingredients, beverage ingredients, hair tonic, etc. The aim of the study is to know Zingiberaceae species diversity in Tembawang Forest, Sumber Karya Village, Teriak District, Bengkayang City, West Kalimantan. The method of the research used exploration with observation in three Tembawang Forest at Sumber Karya Village. The results showed that there were seven species of Zingiberaceae namely E. coccinea, E. elatior,Â E. nasuta, G. atrosanguinea, H. reticulata, Z. multibracteatum, and Z. zerumbet.